Fleeting Echoes of Rebellion. Tactical Innovation in the 2020 Peruvian Agrarian Strike - Manky, Omar (2024)
The 2020 Agrarian Strike emerged as one of the most significant labor mobilizations in Peru over the past decade. A massive nationwide mobilization, the strike achieved the repeal of a law that, for two decades, had granted differentiated rights to agricultural workers compared to their counterparts in other sectors of the formal economy. Based on journalistic sources, documentary evidence, and interviews with key actors, this article delves into the development of this mobilization through the lens of social movement theory. We argue that the strike was a collective action without the support of unions or political organizations, which led to confrontational tactics such as road blockages in the midst of a political crisis. We further observe that the critical nature of the leaders’ discourse and the extensive mobilization failed to produce significant changes in labor relations or union organizational capacity. Consequently, we characterize the strike as a fleeting rebellion—radical in its immediate actions and outcomes, yet unable to propose tangible alternatives for the mid-term. The article discusses the implications of these findings for labor studies in Peru and the broader region.